Elimination of Microcystis aeruginosa Kütz. by modified walnut and peanut shells with phosphoric acid (Bangladesh Journal of Botany, 2018)
The phosphoric acid modified walnut and peanut shell were prepared and applied for the removal of the blue-green alga (Microcystis aeruginosa Kütz.). Orthogonal experiment was used to optimize the modified condition. For the efficient removal, 0.05 g of the modified walnut and peanut shell was added into 50 ml of algal culture and kept standing for 4 hrs. This condition was found best and under which the removal rate of algae can be reached > 90%. At the same time, a comparison between unmodified walnut and peanut shell and modified walnut and peanut shell on the removal of M. aeruginosa cells showed that, unmodified walnut and peanut shell have a removal rate of 31.51 and 29.90%, respectively. On the other hand, the modified walnut and peanut shell showed a removal rate of 96.55 and 93.75%, respectively. Walnut and peanut shells modified with phosphoric acid enhanced the removal efficiency of M. aeruginosa cells. So, the modified walnut and peanut shell were considered as a potential algaecide with high efficiency of obnoxious algae removal from the environment safely.